STUDI POLA OPERASI BENDUNGAN LEUWIKERIS MENGGUNAKAN HEC-RESSIM - Barkah, Jajat Saepul; Ramadan, Anri; Asniar, Novi (JITSi : Jurnal Ilmiah Teknik Sipil, 2022)
Abstract— The Citanduy River area with an area of ​​48,000 ha has a water availability of 5.30 billion m3/year or equivalent to a discharge of 170 m3/s. To optimize this water demand, the Leuwikeris Dam was built. The Leuwikeris Dam is expected to provide 11,216 ha of irrigation water, 0.845 m3/s of raw water, and 20 MW of hydropower for the surrounding area. To meet all water requirements, the dam operation system is an important factor that must be planned. This research method is a study of the dam operation system using HEC-ResSim software. The aim is to analyze the potential water availability in the Leuwikeris Dam and to analyze the optimal use of water resources with the Leuwikeris Dam operation system. The inflow discharge data is taken from data the Cirahong water postal post from 2007-2019. In the Leuwikeris Dam operation simulation study using HEC-ResSim divides the containment boundaries into three zones, namely the dead storage at an elevation of +133 m, the conservation storage at an elevation of +140,568 m, and the flood storage at an elevation of +156,618 m. The simulation results of the operation of the Leuwikeris Dam using HEC-ResSim with an operating time span of 13 years resulted in a river maintenance water requirement of 4.93 m3/s that was met 79%, raw water needs for Tasikmalaya Regency, Ciamis Regency, and Banjar City were 0.845 m3/s 78% can be fulfilled, the need for irrigation water covering an area of ​​11,216 ha 76% and the power capacity of PLTA which in the study is expected to be 15,388 MW can be met by 76%. Keywords — Water resources, Operating System, HEC-ResSim, Leuwikeris Dam. Abstrak— Wilayah Sungai Citanduy dengan luas 48.000 ha memiliki ketersediaan air sebesar 5,30 Milyar m3/tahun atau setara dengan debit sebesar 170 m3/detik. Untuk mengoptimalkan pemanfaatan air tersebut maka di bangun Bendungan Leuwikeris. Bendungan Leuwikeris diharapkan memenuhi penyediaan air irigasi seluas 11.216 ha, air baku 0,845 m3/s dan PLTA sebesar 20 MW untuk daerah sekitar. Untuk memenuhi semua kebutuhan air pola operasi bendungan menjadi faktor penting yang harus direncanakan. Metode penelitian ini adalah studi pola operasi bendungan menggunakan software HEC-ResSim. Tujuannya menganalisis potensi ketersediaan air pada Bendungan Leuwikeris serta menganalisis pemanfaatan sumber daya air dengan pola pengoperasian Bendungan Leuwikeris secara optimal. Data debit inflow diambil dari pos duga air Cirahong dari tahun 2007-2019. Pada studi simulasi operasi Bendungan Leuwikeris menggunakan HEC-ResSim membagi batas tampungan menjadi tiga zona, yaitu zona tampungan bendungan mati pada elevasi +133 m, zona konservasi pada elevasi +140,568 m dan zona tampungan bendungan banjir pada elevasi +156,618 m. Hasil simulasi pengoperasian Bendungan Leuwikeris dengan menggunakan HEC-ResSim dengan rentang waktu pengoperasian selama 13 tahun menghasilkan kebutuhan air pemeliharaan sungai sebesar 4,93 m3/s dapat terpenuhi 79 %, kebutuhan air baku untuk Kabupaten Tasikmalaya, Kabupaten Ciamis dan Kota banjar sebesar 0,845 m3/s dapat terpenuhi 78%, kebutuhan air irigasi seluas 11.216 ha 76 % dan kapasitas daya PLTA yang pada penelitian diharapkan sebesar 15,388 MW dapat terpenuhi sebesar 76%. Kata kunci — Ketersediaan Air, Pola Operasi, HEC-ResSim, Bendungan Leuwikeris